Development of molecular diagnostic methods (LAMP and PCR) for detection of Haemonchus contortus, Fasciola SPP and Trichostrongylus SPP infections in livestock - Mabe, Lerato Tshepiso (University of the Free State, 2012)
Helminths belonging to the genera Haemonchus and Trichostrongylus as well as those of the genus Fasciola are the causative agents of various helminthiases in animals and sometimes in humans. In both host types infections are often acquired through the ingestion of infected food as well as drinking contaminated water. In animals they disrupt the efficient conversion of food material and absorption of nutrients resulting in weakness and death. Infected humans often suffer from intestinal obstruction, insomnia, vomiting, weakness and stomach pains and sometimes temporary asthma. Infections are associated with huge economic losses globally. Diagnosed is achieved through the observation of clinical manifestations. In low infections alternative diagnosis is based on the recovery and identification of faecal eggs and cultivation of L3 by microscopy. More accurate diagnosis has recently been achieved through the use of molecular diagnostic tools such as PCR and LAMP. The aim of this study was to develop rapid, sensitive, specific and accurate molecular diagnostic assays. In particular the study focused on LAMP and PCR for the detection of H. contortus, Fasciola and Trichostrongylus spp. infections in four provinces of South Africa. The first study emphasized on the development of LAMP and PCR assays for detection of H. contortus infections in livestock. LAMP primers that specifically amplify the ITS2 gene of H. contortus were designed from this target gene. This set of primers was used to develop a PCR assay for species-specific gene amplification. Both assays were tested at various reaction conditions to optimize for primer annealing temperature. Sensitivity reactions were conducted using 10 fold serial dilutions of target DNA while primer specificity was determined using DNA extracted from closely related species. For the LAMP assay, the optimum annealing temperature was found to be 60°C and 55°C for the PCR assay. When tested for specificity both assays only amplified target DNA thereby proving to be specific. The sensitivity reactions for both the LAMP and PCR assay yielded a detection limit of 0.42 ng and 10-3 ng respectively as the lowest amount of the target DNA that can be detected by the assays. Screening of field samples by PCR yielded negative results on several occasions while the positive control amplified the target gene as expected. Failure to validate the assay using field samples was attributed to poor quality or lack of DNA. Validation of these assays is central to determining their efficacy and potential importance in diagnosing natural infections with high sensitivity and rapidity. Therefore we recommend close evaluation of DNA extraction from faecal material as well as ways of reducing or eliminating PCR inhibitors. The second study was aimed at developing a LAMP and PCR assay for the detection of Trichostrongylus spp. infections in livestock. In this study, the target gene used for LAMP primer design for genus-specific amplification was the ITS2 gene. Two primer sets were designed and from these primers, two PCR assays were developed. All these assays were subjected to various LAMP and PCR conditions respectively in order to determine suitable annealing temperatures for each assay. Various methods of DNA extraction were evaluated for troubleshooting together with the use of already published PCR primers. Both LAMP and PCR assays did not amplify the target gene at different ranges of annealing temperatures tested. Furthermore, no amplification was achieved from control DNA samples extracted using different methods. Negative results were obtained when the PCR was troubleshot using already published primers. The results achieved with the designed assays may be a direct consequence of improperly designed primers; however, the inability of all primer sets to function for LAMP and PCR as well as for already published primers suggests problems with the extraction of DNA. This can be attributed to ineffective disruption of worms or the presence of DNases that may degrade DNA and inhibit its amplification. The results of this study suggest the need to evaluate pre-treatment of worms prior to DNA extraction. Evaluation of the methods used to reduce the effects of PCR inhibitors during extraction and amplification of DNA may also be considered. The third study was aimed at developing a LAMP and PCR assay for detection of Fasciola spp. infections in livestock. Two sets of primers for species-specific amplification by LAMP were designed by targeting the ITS2 gene of both F. hepatica and F. gigantica. Species-specific PCR assays were developed from the latter primers and gene of the parasites and the assays were then tested at various reaction conditions. A genus-specific PCR assay was subsequently developed and tested. No amplification of DNA was observed with the F.hepatica-specific LAMP assay whereas the assay developed for specific detection of F. gigantica produced false positive results. All PCR assays yielded negative results following many attempts to optimize for primer annealing temperature. Reagent contamination was eliminated as the source of non-specific amplification with LAMP suggesting that improper primer design was a possible cause of this problem. On the other hand failed attempts to optimize all the other assays suggest that there is need to evaluate pre-treatment of worms prior to DNA extraction as well as the methods reducing the effects of PCR inhibitors during amplification. Overall, this study successfully achieved the development and optimization of a LAMP and PCR assay for detection of H. contortus DNA. However, subsequent validation of the assays using field derived samples was not possible. The overall results of this study mostly point to faulty primer design and the presence of PCR inhibitors in extracted DNA samples, extracted from either tissue or faecal samples. According to previous studies the presence of inhibitory substances may interfere with the lysis step, inactivate the thermostable DNA polymerase and even interfere with nucleic acids. Therefore evaluation of more accurate methods of mechanical disruption of the worms, DNA extraction, primer design and the use of amplification facilitators may yield desired results. Therefore, these factors should be taken into account for successful development and validation of the molecular diagnostic tool for detection of helminth infections.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State (Qwaqwa) Campus, 2012
Keywords: Livestock; Veterinary entomology; Livestock -- Diseases; Haemonchus contortus -- Early detection; Polymerase chain reaction -- Diagnostic use